Resin composition and molded article

By combining the fluoropolymer of a specific composition with a methylpropionate-based resin to form a resin combination with a high tensile property and excellent transparency, the problem in the prior art is solved that it is difficult to achieve both properties simultaneously.

JP7667024B2Active Publication Date: 2025-04-22DAIKIN INDUSTRIES LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021128867
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-04-14
Filing Date
2021-08-05
Publication Date
2025-04-22
Estimated Expiration
2038-04-11

AI Technical Summary

Technical Problem

It is difficult for the prior art to achieve high tensileability and excellent transparency of vinylidene fluoride resins and methacrylate resins at the same time.

Method used

A fluoropolymer of a specific composition is used to combine with a methylpropionate-based resin to form a specific resin combination, the fluoropolymer contains ether propylene fluoride units and vinyl fluoride units, with a molar ratio of between 81/19 and 99/1.

Benefits of technology

High tensile properties and excellent transparency of the resin combination are achieved. The tensile properties of the resin combination can reach 30% or more, and the transparency can reach 82.0% T or more.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667024000001
    Figure 0007667024000001
  • Figure 0007667024000002
    Figure 0007667024000002
  • Figure 0007667024000003
    Figure 0007667024000003
Patent Text Reader

Abstract

To provide a resin composition and a molded article which have large tensile elongation and excellent transparency.SOLUTION: The resin composition comprises a fluorine-containing polymer and a methacrylate resin. The mass ratio of the fluorine-containing polymer to the methacrylate resin is 35 / 65-95 / 5. The fluorine-containing polymer contains a vinylidene fluoride unit and a tetrafluoroethylene unit. The molar ratio of the vinylidene fluoride unit to the tetrafluoroethylene unit is 81 / 19-99 / 1.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition and a molded article. [Background technology]

[0002] Since vinylidene fluoride resins are compatible with methacrylate resins, a technique of blending vinylidene fluoride resins with methacrylate resins is known.

[0003] For example, Patent Document 1 describes a molding method for vinylidene fluoride resin in which 1 to 10 parts by weight of an acrylic processing aid for general polyvinyl chloride resin and 0.5 to 3.0 parts by weight of an acrylic high molecular weight lubricant are added to 50 to 100 parts by weight of vinylidene fluoride resin and 0 to 50 parts by weight of methacrylate resin.

[0004] Patent Document 2 describes a resin composition containing 5% by mass or more and 65% by mass or less of the following polymer X and 35% by mass or more and 95% by mass or less of the following polymer Y. Polymer X: Vinylidene fluoride resin. Polymer Y: A copolymer having a domain (y1) that is compatible with polymer X and a domain (y2) that is incompatible with polymer X.

[0005] Patent Document 2 also discloses that the domain (y1) or the domain (y2) contains a macromonomer unit, and that the macromonomer unit preferably contains a methyl methacrylate unit. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 2-102252 [Patent Document 2] International Publication No. 2015 / 146752 Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a resin composition and a molded article having high tensile elongation and excellent transparency. [Means for solving the problem]

[0008] The present inventors have found that a resin composition and a molded article having high tensile elongation and excellent transparency can be obtained by using a fluoropolymer having a specific composition and blending the fluoropolymer with a methacrylate resin, and have thus completed the present invention.

[0009] That is, the present invention relates to a resin composition comprising a fluorine-containing polymer and a methacrylate-based resin, wherein the mass ratio of the fluorine-containing polymer to the methacrylate-based resin is 35 / 65 to 95 / 5, the fluorine-containing polymer contains vinylidene fluoride units and tetrafluoroethylene units, and the molar ratio of the vinylidene fluoride units to the tetrafluoroethylene units is 81 / 19 to 99 / 1.

[0010] In the resin composition of the present invention, the mass ratio is preferably from 45 / 55 to 85 / 15, and the molar ratio is preferably from 85 / 15 to 96 / 4.

[0011] In the resin composition of the present invention, the fluoropolymer preferably has a melt flow rate of 0.1 to 100 g / 10 min.

[0012] The resin composition of the present invention preferably has a tensile elongation of 30% or more when measured at a tensile speed of 100 mm / min, and a light transmittance of 82.0%T or more at a wavelength of 550 nm when measured with a spectrophotometer.

[0013] The present invention also relates to a molded article comprising the above-mentioned resin composition. Effect of the Invention

[0014] The resin composition of the present invention has high tensile elongation and excellent transparency.

[0015] The molded article of the present invention has high tensile elongation and excellent transparency. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present invention will be specifically described below.

[0017] The resin composition of the present invention comprises a fluoropolymer and a methacrylate-based resin, and is characterized in that the mass ratio of the fluoropolymer to the methacrylate-based resin (the fluoropolymer / the methacrylate-based resin) is 35 / 65 to 95 / 5.

[0018] The mass ratio is preferably from 45 / 55 to 85 / 15, more preferably from 55 / 45 to 75 / 25, and further preferably from 65 / 35 to 75 / 25.

[0019] The mass ratio is preferably from 45 / 55 to 85 / 15, more preferably from 55 / 45 to 75 / 25, and even more preferably from 65 / 35 to 75 / 25. When the proportion of the fluoropolymer is high, the material has high tensile elongation.

[0020] Furthermore, the mass ratio is preferably 35 / 65 to 55 / 45, and more preferably 35 / 65 to 45 / 55. When the proportion of the methacrylate resin is high, the material has a higher tensile elongation than the methacrylate resin and is well-balanced with the tensile stress.

[0021] The resin composition of the present invention is characterized in that it comprises the above-mentioned fluorine-containing polymer containing vinylidene fluoride units and tetrafluoroethylene units, in which the molar ratio of vinylidene fluoride units to tetrafluoroethylene units (vinylidene fluoride units / tetrafluoroethylene units) is 81 / 19 to 99 / 1.

[0022] The molar ratio is preferably from 85 / 15 to 96 / 4, more preferably from 88 / 12 to 95 / 5, and further preferably from 91 / 9 to 94 / 6.

[0023] In this specification, the content of each monomer unit can be calculated by appropriately combining NMR and elemental analysis depending on the type of monomer.

[0024] The above-mentioned fluorine-containing polymer may contain, in addition to vinylidene fluoride units and tetrafluoroethylene units, polymerization units based on a monomer copolymerizable with vinylidene fluoride and tetrafluoroethylene. In order to achieve the effects of the present invention, a copolymer of vinylidene fluoride and tetrafluoroethylene is sufficient, but a monomer copolymerizable with vinylidene fluoride and tetrafluoroethylene can be further copolymerized to an extent that does not impair the excellent transparency and tensile elongation of the resin composition consisting of the above-mentioned copolymer.

[0025] In the above fluorine-containing polymer, the total of vinylidene fluoride units and tetrafluoroethylene units is preferably 60 to 100 mol % relative to 100 mol % of all polymerized units, and polymerized units based on monomers copolymerizable with vinylidene fluoride and tetrafluoroethylene are preferably 0 to 40 mol %. More preferably, the total of vinylidene fluoride units and tetrafluoroethylene units is 80 to 100 mol % relative to 100 mol % of all polymerized units, and polymerized units based on monomers copolymerizable with vinylidene fluoride and tetrafluoroethylene are preferably 0 to 20 mol %.

[0026] Examples of monomers copolymerizable with vinylidene fluoride and tetrafluoroethylene include fluorine-containing olefins such as chlorotrifluoroethylene, trifluoroethylene, monofluoroethylene, hexafluoropropylene, and perfluoro(alkyl vinyl ether); fluorine-containing acrylates; and fluorine-containing monomers having functional groups.

[0027] Examples of monomers that can be copolymerized with the vinylidene fluoride and tetrafluoroethylene include unsaturated dibasic acid monoesters, such as maleic acid monomethyl ester, citraconic acid monomethyl ester, citraconic acid monoethyl ester, maleic acid, maleic anhydride, and vinylene carbonate, as described in JP-A-6-172452, and also -SO3M, -OSO3M, -COOM, -OPO3M (M represents an alkali metal) and an amine polar group, -NHR, as described in JP-A-7-201316. a , -NR b R c (R a , R b , R c represents an alkyl group), an amide group (-CO-NR' (R and R' are the same or different and each represents a hydrogen atom or an alkyl group which may have a substituent), an amide bond (-CO-NR"- (R" represents a hydrogen atom, an alkyl group which may have a substituent, or a phenyl group which may have a substituent)) and a carbonyl group. Among these compounds having a hydrophilic polar group, compounds having an amide group and a carbonyl group are preferred, and compounds having an amide group are particularly preferred.

[0028] In a compound having an amide group, the amide group is a group represented by -CO-NRR'. R and R' are the same or different and each is a hydrogen atom or an alkyl group which may have a substituent. When R and R' are alkyl groups, they may be linear, cyclic or branched. The number of carbon atoms in the alkyl group is preferably 1 to 30, more preferably 1 to 20. Examples of the substituent include a halogen atom, an alkoxy group having 1 to 30 carbon atoms, and an aryl group having 6 to 30 carbon atoms.

[0029] The compound having an amide group is not particularly limited as long as it has one or more polymerizable carbon-carbon double bonds and one or more amide groups in the molecule, but may be any compound having the following general formula (1):

[0030] [ka]

[0031] (In the formula, X 1 are the same or different and each represents a hydrogen atom or an alkyl group which may have a substituent. 2 represents a hydrogen atom or an alkyl group which may have a substituent. Y represents a single bond or an alkylene group which may have a substituent. R 1 and R 2 are the same or different and each represents a hydrogen atom or an alkyl group which may have a substituent.) It is preferable that the monomer has one polymerizable carbon-carbon double bond and one amide group in the molecule. 1 Each of the two X's in the above general formula (1) is a hydrogen atom or an alkyl group. 1 may be the same or different from each other. The alkyl group may or may not have a substituent. The alkyl group may be linear, cyclic, or branched. Examples of the alkyl group include the same groups as those described above for R and R'.

[0032] Above X 1 In the above general formula (1), X is preferably a hydrogen atom or a halogen atom, and particularly preferably a hydrogen atom. 2 is a hydrogen atom or an alkyl group. The alkyl group may or may not have a substituent. The alkyl group may be linear, cyclic, or branched. The alkyl group may be any of the above-mentioned X 1 Examples of the above-mentioned X 2 Among them, a hydrogen atom or a methyl group is preferable. Y in the above general formula (1) is a single bond or an alkylene group. The above alkylene group may or may not have a substituent. In addition, the above alkylene group may be linear, cyclic, or branched. The number of carbon atoms in the above alkylene group is preferably 1 to 30, and more preferably 1 to 25.

[0033] The above-mentioned substituents include the above-mentioned X1 The same as those mentioned above for R in the above general formula (1) can be mentioned. 1 and R 2 is a hydrogen atom or an alkyl group. 1 and R 2 may be the same or different from each other. The alkyl group may or may not have a substituent. The alkyl group may be linear, cyclic, or branched. The alkyl group may be any of the above X 1 Examples of the above-mentioned R 1 and R 2 Among these, a hydrogen atom or a halogen atom is preferable, and a hydrogen atom is particularly preferable.

[0034] As the compound having an amide group, there may be mentioned, among others, a compound represented by the following general formula (2):

[0035] [ka]

[0036] (In the formula, X 3 R represents a hydrogen atom or a methyl group. 3 and R 4 are the same or different and each represents a hydrogen atom or an alkyl group which may have a substituent. 3 and R 4 Specific examples of R in the above general formula (1) are 1 and R 2 This is similar to what was said about

[0037] The above-mentioned (meth)acrylamides include (meth)acrylamide and its derivatives.Specific examples include (meth)acrylamide, N-methyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-tert-butyl(meth)acrylamide, N-phenyl(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide, 4-acryloylmorpholine, diacetone(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, and 2-(meth)acrylamide-2-methylpropanesulfonic acid.Among these, N-tert-butyl(meth)acrylamide is particularly preferred.

[0038] In the compound having an amide bond, the amide bond is a bond represented by -CO-NR"-, or may be a bond represented by -CO-NR"-CO-. R" represents a hydrogen atom, an alkyl group which may have a substituent, or a phenyl group which may have a substituent. The alkyl group and the substituent may be the same as the alkyl group and the substituent exemplified as R in the compound having an amide group. Examples of the compound having an amide bond include N-vinylacetamide derivatives such as N-vinylacetamide and N-methyl-N-vinylacetamide; and maleimide derivatives such as maleimide, N-butylmaleimide, and N-phenylmaleimide. Of these, N-vinylacetamide is preferable.

[0039] The monomers copolymerizable with the vinylidene fluoride and tetrafluoroethylene are CH2=CH-CH2-Y, CH2=C(CH3)-CH2-Y, CH2=CH-CH2-O-CO-CH(CH2COOR)-CH2-Y, d )-Y, CH2=CH-CH2-O-CH2-CH(OH)-CH2-Y, CH2=C(CH3)-CO-O-CH2-CH2-CH2-Y, CH2=CH-CO-O-CH2-CH2-Y, CH2=CHCO-NH-C(CH3)2-CH2-Y (Y is a hydrophilic polar group, and R drepresents an alkyl group). n -OH (3≦n≦8) can also be used.

[0040] [ka]

[0041] CH2=CH-CH2-O-(CH2-CH2-O) n -H(1≦n≦14), CH2=CH-CH2-O-(CH2-CH(CH3)-O) n Hydroxylated allyl ether monomers such as -H(1≦n≦14) and carboxylated and / or (CF2) n Allyl ether and ester monomers substituted with -CF3 (3≦n≦8), e.g. CH2=CH-CH2-O-CO-C2H4-COOH, CH2=CH-CH2-O-CO-CH 10 -COOH, CH2=CH-CH2-O-C2H4-(CF2) n CF3, CH2=CH-CH2-CO-O-C2H4-(CF2) n CF3, CH2=C(CH3)-CO-O-CH2-CF3, etc. can also be used as copolymerizable monomers.

[0042] By the way, it has been inferred from previous research that, in addition to compounds containing polar groups as described above, the transparency and flexibility of a resin composition can be imparted by slightly reducing the crystallinity of a copolymer of vinylidene fluoride and tetrafluoroethylene. For example, unsaturated hydrocarbon monomers such as ethylene and propylene (CH2=CHR, where R is a hydrogen atom, an alkyl group, or a halogen such as Cl), and fluorine monomers such as trifluorochloroethylene, hexafluoropropylene (HFP), hexafluoroisobutene, 2,3,3,3-tetrafluoropropene, CF2=CF-OC n F 2n+1 (n is an integer of 1 or more), CH2=CF-C n F 2n+1 (n is an integer of 1 or more), CH2=CF-(CF2CF2) nH (n is an integer of 1 or more), and CF2=CF-O-(CF2CF(CF3)O) m -C n F 2n+1 (m and n are integers of 1 or more) can also be used. Other formulas:

[0043] [ka]

[0044] (wherein Y is -CHOH, -COOH, a carboxylate, a carboxy ester group or an epoxy group; X and X 1 are the same or different and are each a hydrogen atom or a fluorine atom; R f represents a divalent fluorine-containing alkylene group having 1 to 40 carbon atoms or a divalent fluorine-containing alkylene group containing an ether bond having 1 to 40 carbon atoms), can also be used.

[0045] Thus, the above-mentioned fluorine-containing polymer may contain other polymer units in addition to vinylidene fluoride units and tetrafluoroethylene units, but more preferably consists of only vinylidene fluoride units and tetrafluoroethylene units.

[0046] The above-mentioned fluoropolymer has a melting point of preferably from 100 to 165°C, more preferably from 110 to 160°C, and further preferably from 115 to 155°C.

[0047] The melting point is determined as the temperature corresponding to the maximum value on the heat of fusion curve when the temperature is raised to 200°C at a rate of 10°C / min, cooled to 50°C, and then raised again to 200°C using a differential scanning calorimetry (DSC) device.

[0048] The above fluoropolymer preferably has a melt flow rate (MFR) of 0.1 g / 10 min or more. More preferably, it is 1.0 g / 10 min or more, and even more preferably, it is 5.0 g / 10 min or more. The above fluoropolymer preferably has an MFR of 100 g / 10 min or less. More preferably, it is 50 g / 10 min or less, and even more preferably, it is 30 g / 10 min or less. The above fluoropolymer preferably has an MFR of 0.1 to 100 g / 10 min. More preferably, it is 1.0 to 50 g / 10 min. Even more preferably, it is 5.0 to 30 g / 10 min. If it is lower than these ranges, the moldability may be extremely reduced, and if it is higher than these ranges, the transparency may not be exhibited when melt-kneaded, and the mechanical strength may be significantly reduced.

[0049] The MFR of the fluoropolymer was measured at a temperature of 230° C. under a load of 5 kg using a melt index tester in accordance with ASTM D 1238.

[0050] The methacrylate resin is a resin containing a methacrylate unit, and is preferably at least one selected from the group consisting of a homopolymer of methyl methacrylate and a copolymer of methyl methacrylate and another comonomer.

[0051] Examples of the comonomer include methyl acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, n-octyl (meth)acrylate, dodecyl (meth)acrylate, stearyl (meth)acrylate, isobornyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, and benzyl (meth)acrylate. Examples of the monomer units include alkyl (meth)acrylates such as acrylate, aromatic vinyl monomers such as styrene, α-methylstyrene, p-methylstyrene, o-methylstyrene, and t-butylstyrene, vinyl cyanide monomers such as acrylonitrile and methacrylonitrile, glycidyl group-containing monomers such as glycidyl (meth)acrylate, vinyl carboxylate monomers such as vinyl butyrate, olefin monomers such as ethylene, propylene, and isobutylene, diene monomers such as butadiene and isoprene, and unsaturated carboxylic acids such as maleic acid and maleic anhydride. Here, "(meth)acrylate" refers to "acrylate" or "methacrylate".

[0052] The methacrylate resin may be a resin whose melting point is not detectable. The presence or absence of the melting point can be confirmed by the presence or absence of a maximum value in the heat of fusion curve when the temperature is increased to 200°C at a rate of 10°C / min, cooled to 50°C, and then increased to 200°C again using a differential scanning calorimeter (DSC).

[0053] The methacrylate resin preferably has a melt flow rate (MFR) of 0.1 g / 10 min or more. More preferably, it is 0.5 g / 10 min or more, and even more preferably, it is 1 g / 10 min or more. The MFR of the methacrylate resin is preferably 100 g / 10 min or less. More preferably, it is 70 g / 10 min or less, and even more preferably, it is 50 g / 10 min or less. The MFR of the methacrylate resin is preferably 0.1 to 100 g / 10 min. More preferably, it is 0.5 to 70 g / 10 min, and even more preferably, it is 1.0 to 50 g / 10 min. If it is lower than these ranges, the moldability may be extremely reduced, and if it is higher than these ranges, the transparency may not be exhibited when melt-kneaded, and the mechanical strength may be significantly reduced.

[0054] The MFR of the methacrylate resin was measured at a temperature of 230° C. under a load of 5 kg using a melt index tester conforming to ASTM D 1238.

[0055] The above-mentioned resin composition may also contain other components, such as a filler, a plasticizer, a processing aid, a release agent, a pigment, a flame retardant, a lubricant, a light stabilizer, a weather resistance stabilizer, a heat resistance stabilizer, an antiblocking agent, an antibacterial agent, an antifungal agent, a bluing agent, a conductive agent, an antistatic agent, an ultraviolet absorbing agent, an antioxidant, a foaming agent, a fragrance, an oil, a softening agent, and a dehydrofluorination agent, provided that the object of the present invention is not impaired.

[0056] The resin composition may contain the fluorine-containing polymer and the methacrylate resin in a total amount of 95 to 100 mass%, may contain 97 mass% or more, or may contain 99 mass% or more. Containing 100 mass% of the fluorine-containing polymer and the methacrylate resin means that the other components are not substantially contained.

[0057] The resin composition may be a resin composition whose melting point is not detectable because it is a compatible system in a part of the composition range. In addition, when the melting point is detectable, it is preferably 100 to 165°C. More preferably, it is 110 to 160°C, and further preferably, it is 115 to 155°C. The melting point is determined as the temperature corresponding to the maximum value in the heat of fusion curve when the temperature is increased to 200°C at a rate of 10°C / min, cooled to 50°C, and then increased to 200°C again using a differential scanning calorimetry (DSC) device.

[0058] The resin composition has an MFR of preferably 0.1 to 100 g / 10 min, more preferably 0.5 to 70 g / 10 min, and even more preferably 1.0 to 50 g / 10 min. The MFR is measured at a temperature of 230° C. and a load of 5 kg using a melt index tester conforming to ASTM D 1238.

[0059] The resin composition has a large tensile elongation and is easily stretched. The resin composition may have a tensile elongation of 30% or more at 23°C. More preferably, the tensile elongation is 50% or more. Even more preferably, the tensile elongation is 70% or more. The tensile elongation can be measured by preparing a dumbbell piece (ASTM Type V) from the resin composition by injection molding and conducting a tensile test at a temperature of 23°C and a test speed of 100 mm / min.

[0060] The resin composition has a large light transmittance and excellent transparency. The resin composition may have a light transmittance of 82.0%T or more at a wavelength of 550 nm. More preferably, the resin composition may have a light transmittance of 84.0%T or more. Even more preferably, the resin composition may have a light transmittance of 86.0%T or more. If the transmittance is lower than the above, sufficient transparency may not be obtained. The transmittance can be measured by producing a 1 mm thick sheet from the resin composition by compression molding, and irradiating the sheet with a light beam of 550 nm using a spectrophotometer.

[0061] The resin composition preferably has a tensile elongation of 30% or more when measured at a tensile speed of 100 mm / min, and a light transmittance of 82.0%T or more at a wavelength of 550 nm when measured by a spectrophotometer. A resin composition having both such a large tensile elongation and a high light transmittance has not been known in the past. The resin composition more preferably has a tensile elongation of 40% or more when measured at a tensile speed of 100 mm / min, and a light transmittance of 83.0%T or more at a wavelength of 550 nm when measured by a spectrophotometer. The resin composition more preferably has a tensile elongation of 50% or more when measured at a tensile speed of 100 mm / min, and a light transmittance of 84.0%T or more at a wavelength of 550 nm when measured by a spectrophotometer. The resin composition is useful for various optical applications.

[0062] The shape of the resin composition is not particularly limited, and may be in the form of powder, flakes, or pellets. From the viewpoints of ease of production and excellent handleability, the pellet form is preferred.

[0063] The resin composition can be prepared by mixing the fluoropolymer and the methacrylate resin. For the mixing, a mixer such as a compounding mill, a Banbury mixer, a Henschel mixer, a pressure kneader, or an extruder can be used, and from the viewpoint of easily and sufficiently mixing the resins, it is preferable to use a twin-screw extruder.

[0064] The mixing is preferably carried out in a molten state so that the resins can be thoroughly mixed. For example, the resins can be melted by heating to a temperature equal to or higher than the highest of the melting point of the fluoropolymer and the melting point or softening point of the methacrylate resin.

[0065] The present invention also relates to a molded article comprising the above-mentioned resin composition. The molded article is obtained by molding the above-mentioned resin composition.

[0066] Examples of the molding method include compression molding, extrusion molding, film molding, tube molding, multi-layer molding, blow molding, vacuum molding, transfer molding, injection molding, roto molding, roto-lining molding, spinning molding, and electrostatic coating. EXAMPLES

[0067] Next, the present invention will be described with reference to examples, but the present invention is not limited to these examples.

[0068] The values ​​in the examples were measured by the following methods.

[0069] Copolymer Composition A nuclear magnetic resonance spectrometer AC300 (manufactured by Bruker-Biospin) was used, and the measurement temperature was set at the melting point of the polymer + 20°C. 19 F-NMR measurement was performed, and the integral value of each peak and, depending on the type of monomer, elemental analysis were appropriately combined to determine the value.

[0070] Comparative Example 1 10% by mass of a copolymer of vinylidene fluoride (VdF) and tetrafluoroethylene (TFE) (resin A: VdF / TFE=93mol% / 7mol%, melting point: 143℃, MFR: 30.5g / 10min) and 90% by mass of polymethyl methacrylate (PMMA) (manufactured by Mitsubishi Rayon Co., Ltd., product name: ACRYPET, model: VH001, melting point: not detected, MFR: 2.4g / 10min) were pre-dried at 80℃, dry-blended, and then extruded at a maximum temperature of 220℃ using a Φ25mm twin-screw extruder to obtain a pellet-shaped composite material. Then, a 1mm-thick press sheet was produced by compression molding. The compression molding was performed under the conditions of preheating at 200℃ / 10min, molding at 220℃ / 5MPa / 1min, and cooling with water / 5MPa / 5min. Furthermore, a dumbbell piece (ASTM type V) was produced by injection molding. Injection molding was performed at a resin temperature of 160-220°C and a mold temperature of 30-40°C.

[0071] Comparative Example 2 A pellet-shaped composite material and its molded products (press sheet and dumbbell piece) were obtained in the same manner as in Comparative Example 1, except that the blending amount of Resin A was changed to 30 mass % and the blending amount of PMMA was changed to 70 mass %.

[0072] Example 1 A pellet-shaped composite material and a molded product thereof were obtained in the same manner as in Comparative Example 1, except that the blending amount of Resin A was changed to 50% by mass and the blending amount of PMMA was changed to 50% by mass.

[0073] Example 2 A pellet-shaped composite material and a molded product thereof were obtained in the same manner as in Comparative Example 1, except that the blending amount of Resin A was changed to 60% by mass and the blending amount of PMMA was changed to 40% by mass.

[0074] Example 3 A pellet-shaped composite material and a molded product thereof were obtained in the same manner as in Comparative Example 1, except that the blending amount of Resin A was changed to 70% by mass and the blending amount of PMMA was changed to 30% by mass.

[0075] Example 4 A pellet-shaped composite material and a molded product thereof were obtained in the same manner as in Comparative Example 1, except that the blending amount of Resin A was changed to 80% by mass and the blending amount of PMMA was changed to 20% by mass.

[0076] Example 5 A pellet-shaped composite material and its molded body were obtained in the same manner as in Comparative Example 1, except that 70 mass% of a copolymer of VdF and TFE (resin B: VdF / TFE=93 mol% / 7 mol%, melting point: 141°C, MFR: 5.8 g / 10 min) and 30 mass% of PMMA were used.

[0077] Comparative Example 3 A pellet-shaped composite material and a molded product thereof were obtained in the same manner as in Comparative Example 1, except that 50 mass % of a copolymer of VdF and TFE (resin C: VdF / TFE=80 mol % / 20 mol %) and 50 mass % of PMMA were used.

[0078] Comparative Example 4 A pellet-shaped composite material and a molded product thereof were obtained in the same manner as in Comparative Example 3, except that the blending amount of Resin C was changed to 70% by mass and the blending amount of PMMA was changed to 30% by mass.

[0079] Comparative Example 5 A pellet-shaped composite material and a molded product thereof were obtained in the same manner as in Comparative Example 1, except that 50 mass % of a VdF polymer (PVdF:VdF / TFE=100 mol % / 0 mol %) and 50 mass % of PMMA were used.

[0080] Comparative Example 6 A pellet-shaped composite material and a molded product thereof were obtained in the same manner as in Comparative Example 5, except that the blending amount of PVdF was changed to 70 mass % and the blending amount of PMMA was changed to 30 mass %.

[0081] Comparative Example 7 After pre-drying PMMA overnight at 80°C, a 1 mm thick press sheet was produced by compression molding. Dumbbell pieces were then produced by injection molding. The molding conditions were the same as those of Comparative Example 1.

[0082] Comparative Example 8 Resin A was pre-dried overnight at 80°C, and then compressed into a pressed sheet having a thickness of 1 mm. Dumbbell pieces were then produced by injection molding. The molding conditions were the same as those of Comparative Example 1.

[0083] Comparative Example 9 Resin B was pre-dried overnight at 80° C., and then compressed into a pressed sheet having a thickness of 1 mm. Dumbbell pieces were then produced by injection molding. The molding conditions were the same as those of Comparative Example 1.

[0084] Comparative Example 10 Resin C was pre-dried overnight at 80° C., and then compressed into a pressed sheet having a thickness of 1 mm. Dumbbell pieces were then produced by injection molding. The molding conditions were the same as those of Comparative Example 1.

[0085] Comparative Example 11 After pre-drying the PVdF overnight at 80°C, a 1 mm thick press sheet was produced by compression molding. Further, a dumbbell piece was produced by injection molding. The molding conditions were the same as those of Comparative Example 1.

[0086] Evaluation method for molded products (Tensile test) Using dumbbell pieces (ASTM Type V) made by injection molding, the tensile stress and tensile elongation were measured at a temperature of 23°C and a test speed of 100 mm / min using a universal material testing machine (manufactured by A&D Co., Ltd.) with reference to ASTM D638.

[0087] (Light transmittance measurement) The light transmittance of the pressed sheet (1 mm thick) produced by compression molding was measured with a spectrophotometer (manufactured by Hitachi High-Tech Science Corp.) The light transmittance was measured at a wavelength of 550 nm, and the blank was air.

[0088] (Melt flow rate measurement) The resin composition (pellets) obtained by the twin-screw extruder was used to measure the MFR with a melt index tester (manufactured by Toyo Seiki Seisakusho, Ltd.) at a temperature of 230° C. and a load of 5 kg.

[0089] (Differential Scanning Calorimetry) The melting point of the resin composition (pellets) obtained by the twin-screw extruder was measured by a differential scanning calorimetry (DSC) device. The melting point was determined as the temperature corresponding to the maximum value on the heat of fusion curve when the temperature was raised to 200°C at a rate of 10°C / min, lowered to 50°C, and then raised again to 200°C. Moreover, resin compositions for which no temperature corresponding to a maximum value was detected are indicated with (-) in the table.

[0090] [Table 1] [Industrial Applicability]

[0091] INDUSTRIAL APPLICABILITY The resin composition of the present invention has good elongation and excellent transparency, and therefore can be suitably used in a wide range of fields, such as lamination films, adhesive tape films, agricultural films for tunnel houses and pipe houses, electrical insulating films, heavy packaging films, solar cell films, optical films, liquid crystal display films, decorative films, shrink films, automotive parts, home appliance parts, medical parts, building parts, plastic optical fibers, automotive headlamps, touch panels, and film sensors.

[0092] Since the molded article of the present invention has good elongation and excellent transparency, it can be suitably used as a lamination film, a film for adhesive tapes, an agricultural film for tunnel houses and pipe houses, an electrical insulating film, a heavy-duty packaging film, a film for solar cells, an optical film, a film for liquid crystal displays, a design film, a shrink film, an automobile component, a home appliance component, a medical component, a building component, a plastic optical fiber, an automobile headlamp, a touch panel, a film sensor, and the like.

Claims

1. The composition includes a fluorine-containing polymer and a methacrylate resin, a mass ratio of the fluorine-containing polymer to the methacrylate resin is 45 / 55 to 75 / 25, the fluorine-containing polymer contains vinylidene fluoride units and tetrafluoroethylene units, and a molar ratio of the vinylidene fluoride units to the tetrafluoroethylene units is 81 / 19 to 99 / 1, The tensile elongation measured at a tensile speed of 100 mm / min is 30% or more, A composite material for molding, characterized in that it is in the form of a powder, flake, or pellet.

2. A composite material for molding as described in claim 1, wherein the molar ratio is 85 / 15 to 96 / 4.

3. 3. The composite material for molding according to claim 1, wherein the fluorine-containing polymer has a melt flow rate of 0.1 to 100 g / 10 min.

4. 4. The composite material for molding according to claim 1, 2 or 3, which has a light transmittance of 82.0% T or more at a wavelength of 550 nm as measured with a spectrophotometer.

5. A molded article comprising the composite material for molding according to claim 1, 2, 3 or 4.

Citation Information

Patent Citations

  • Molding of vinylidene fluoride resin

    JP1990102252A

  • Optical phase difference plate and production thereof

    JP1991015005A

  • Vinylidene fluoride-based copolymer resin film

    JP2005042066A

  • Film, method for producing same, laminated film or sheet, and laminate

    WO2011142453A1

  • Method for producing retardation film

    WO2015072486A1